Fallopian Tube Recanalization (F.T.R): application of Interventional Radiology (I.R) post hysterosalpingography in management of female infertility at rural hospital - Mohan, Abhinav Amarnath; Sharma, Gaurav O.; Banode, Pankaj J. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Infertility is defined as inability to conceive even after 1 year of unprotected intercourse. Tubal blockage is one of the common causes of primary as well as secondary infertility in females. Fallopian tube recanalization (FTR) an interventional radiological procedure is one of the most promising, effective, minimally invasive and cost-effective technique in patients having infertility owing to tubal blockage. The aim is to study the cause, hysterosalpingography findings, and outcome of fallopian tube recanalization by interventional radiological procedure in patients with tubal-blockage presenting with infertility. Methods: This was a prospective observational study of women with primary or secondary infertility presenting to interventional radiology department. The patients either had already undergone hysterosalpingography (HSG) or came for HSG. Fallopian tube recanalization was done as per institutional protocol. Hysterosalpingography abnormalities, outcome and complications of fallopian tube recanalization procedure were studied. Results: In this study of 87 patients unilateral or bilateral tubal blockages were seen in 16 and 24 patients respectively. Majority of the patients had Segment I proximal block. Bilateral recanalization could be successfully done in 12 patients (24 tubes) with bilateral Proximal Tubal Blockage (PTO). Unilateral recanalization was possible in 12 patients (tubes) with unilateral proximal block and 8 tubes with bilateral proximal tubal block. 10 tubes with PTO could not be recanalized. 5 cases diagnosed with bilateral Distal Tubal Block (DTO), recanalization was not attempted and were referred for appropriate gynecological management. Minor complications were noted in 8 patients while no major procedure related complications were observed. Conclusions: Fallopian tube recanalization (by interventional radiology procedure) in patients with fallopian tube blockage diagnosed on HSG is found to be cost effective, minimally invasive and have low complication rate. It is associated with excellent outcome in terms of technical success and improved conception rate.